Challenges and Innovation: Exploring the Impact of Transformational Leadership and Teacher Creativity - Nurlaelah, Nurlaelah; Rosyidi, Unifah; Muhab, Sukro; Ripki, Ahmad Jauhari Hamid (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
This study investigates the impact of transformational leadership on teachers' creativity at Madrasah Ibtidaiyah in Karawang Regency. Most teachers adhere to conventional teaching approaches and do not incorporate novel concepts or advancements, as evidenced by the 65% success rate. The data was analyzed using quantitative methodology, which included surveys and analytical techniques. The study found that transformational leadership significantly impacted teacher creativity. The T-Statistics values of 3.331 exceeded the critical T-table value of 1.699, and the P-Values of 0.000 were less than the significance level of 0.05. The research hypothesis states that transformational leadership positively affects teacher creativity in Karawang.